Preclinical Biosafety Evaluation of Cell-based Therapies: Emerging Global Paradigms. (January 2015) - Basu, Joydeep; Assaf, Basel T.; Bertram, Timothy A.; Rao, Mahendra
Cell-based therapies have the potential to treat a diversity of disease conditions, many representing significant and long-standing unmet medical needs. Certain properties of cell-based therapies, such as differentiation potential and proliferative potential, present safety concerns uniquely distinct from those of small molecule drugs and other macromolecule biologics. These cellular products carry risks associated with localized host tissue response, long-term persistence, ectopic tissue formation, differentiation to undesirable cell and tissue types, uncontrollable biodistribution, tumorigenicity, and immunogenicity. Such risks are generally evaluated in preclinical animal model studies as part of a comprehensive safety program prior to administration in humans. However, safety assessment for these products can be challenging because of inconsistent approaches to product characterization, inadequately defined product parameters that anticipate adverse events, and the lack of standardized approaches in evaluating in vivo host responses. In this symposium, we introduced cell-based therapies as an emerging product class to the Society of Toxicologic Pathology (STP) and highlighted key challenges for consideration during product biosafety evaluation.